An environmental noise study in the industrial, commercial, residential areas and arterial roads in western Bogotá, Colombia - Guevara, Marco Andrés; Guevara, Fredy Alejandro (Revista de Investigación Agraria y Ambiental, 2018)
Noise pollution as byproduct of development and urban activity is related with a great amount of economic, social and cultural variables, whose importance as stressing, and possible even dangerous, agent in human life has come to be recognized in the last decades. In this case the city of Bogotá is a capital city of Colombia, located in the center of the country. Is the largest city in Colombia and has a surface extension area of 1,580 km2. Bogotá is a very variable city in terms of economic and social level location, and use of soils in the city planning. The factors mentioned above makes Bogotá a very complex analysis system for sound and noise pollution studies. Due the size of the city, in this study the western area of the capital district is analyzed through a sound measurements in 7 different selected types of areas, involving commercial, transportation, industrial, residential and arterial roads. This study allowed to identify the arterial roads as one important source of noise in the city, possibly mainly due to the traffic o heavy vehicles inside the city. The max harmful levels of sound reach values of about 85 dB in the mentioned locations (Av. Ciudad de Cali, Av. Cll 13 arterial roads and Salitre – El Greco Transmilenio Station).